2023
DOI: 10.3389/fspor.2023.1116293
|View full text |Cite
|
Sign up to set email alerts
|

High-speed running and sprinting in professional adult soccer: Current thresholds definition, match demands and training strategies. A systematic review

Abstract: The aims of this systematic review were (1) to summarize the evidence on absolute velocity thresholds used to classify high-speed running and sprinting, (2) to examine the existing evidence about the individualized thresholds approach, (3) to describe high-speed and sprint running distance match demands, and (4) to provide training strategies for eliciting HSR and sprinting during training sessions in professional adult soccer. This systematic review was conducted following the PRISMA 2020 guidelines. After th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
31
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 35 publications
(34 citation statements)
references
References 86 publications
3
31
0
Order By: Relevance
“…These suggestions are supported by previous research that found very similar RPE scores during soccer-specific training protocols ( 30 ), although the accelerations and HSR demands of these formats were significantly different among them. The data reported in the literature ( 8 , 12 , 30 ), in addition to what found in the current research suggest the necessity for practitioners of assessing external load parameters in soccer to have a more complete understanding of players' training load.…”
Section: Resultssupporting
confidence: 68%
See 1 more Smart Citation
“…These suggestions are supported by previous research that found very similar RPE scores during soccer-specific training protocols ( 30 ), although the accelerations and HSR demands of these formats were significantly different among them. The data reported in the literature ( 8 , 12 , 30 ), in addition to what found in the current research suggest the necessity for practitioners of assessing external load parameters in soccer to have a more complete understanding of players' training load.…”
Section: Resultssupporting
confidence: 68%
“…It is important for coaches and sport scientists to track the external and internal demands of training to enhance physical capacity ( 3 , 9 ). External load is commonly monitored using global navigation satellite system (GNSS) units across elite and semi-professional soccer teams ( 10 12 ). GNSS units acquire and track multiple satellite systems (e.g., Global Positioning System, GLONASS) and have evolved to provide practitioners with a more accurate and holistic understanding of the demands placed upon soccer players ( 10 , 13 ).…”
Section: Introductionmentioning
confidence: 99%
“…End-of-season points may be a more sensitive scalar measure, 31 and thus provide a more accurate reflection of team performance, compared to the ordinal nature of final league ranking. Possession and physical data for each team were averaged based on all available matches within that specific season (34 ± 5 matches, range [23][24][25][26][27][28][29][30][31][32][33][34][35][36][37][38]. Therefore, possession and physical metrics were derived from a total of 1374 league matches (2016/17 n = 255, 2017/18 n = 380, 2018/19 n = 371 and 2019/20 n = 368).…”
Section: Sample and Data Collectionmentioning
confidence: 99%
“…During these periods, the following physical metrics were derived: total distance covered as well as within specific speed categories: distance covered walking (0.16-1.97 m⋅s −1 ), jogging (1.97-3.97 m⋅s −1 ), running (3.97-5.47 m⋅s −1 ), high speed (5.47-7.0 m⋅s −1 ), and sprinting (≥7.0 m⋅s −1 ). 34,35 Total distance covered during whole match time (for reference with previous work), and distance covered in total during BIP, and when in-possession/ out-of-possession during BIP, were measured in absolute terms (m). These distances were first calculated on a team basis (i.e., the physical metrics of all outfield players for each team involved in the match were summed, irrespective of individual player identities and substitutions).…”
Section: Data Preparation and Variablesmentioning
confidence: 99%
“…Of the wearable devices available, global navigation satellite systems (GNSS) are the most commonly used (25,29). Global navigation satellite systems units allow for the analysis of external load metrics such as total distance, accelerations, decelerations, sprinting distance, and so on (1,6,23,24). Such information is used to help coaches and sport scientists make informed decisions around modifying training sessions, evaluating the intensity of drills, and adapting training load at the individual level (23,28,37).…”
Section: Introductionmentioning
confidence: 99%